Pengembangan Simulasi Binary Tree berbasis CAI Untuk Pembelajaran Matematika Diskrit - Agustini, Ketut (Prosiding SNATIKA Vol 01 (2011), 2011)
This study aims to design and implement simulation-based Binary Tree Computer Aided Instruction (CAI) that can be used as a tool of effective interaction in the learning Discrete Mathematics. The method used in this research is the development of research methods (research and development), where the development of the selected design is to use the Dick & Carey Model. Because the main outputs produced in the form of a software research, then in the process of media development has been equipped with special methods of software development using the Software Development Life Cycle (SDLC) with Waterfall-based models. To be validated by academic and scientific software products resulting from this development process will be validated and tested through three stages of testing the product testing techniques (technical test) as a software, carried out in accordance with a testing procedure based on standard methods of software with the Waterfall SDLC-based models, testing the product as a medium of learning, through expert review by media experts, and will be carried out field tests on a small group of faculty and students of IT Department of Education Undiksha Singaraja, in accordance with the standards of evaluation of the design development of Dick and Carey Model. Research results indicate that the Binary Tree Simulation-based CAI either used as a tool of effective interaction in the learning Discrete Mathematics. Â  Keywords : Binary Tree, Simulation, Computer Aided Instruction (CAI), Discrete Mathematics.